Envisioning a role for nuclear actin in prophase I spermatocytes - Petrusová, Jana; Manning, Jasper; Filipp, Dominik (Frontiers in Cell and Developmental Biology, 2023)
Actin is a multi-functional protein that is involved in numerous cellular processes including cytoskeleton regulation, cell migration, and cellular integrity. In these processes, actin's role in respect to its structure, complex mechanical, and protein-binding properties has been studied primarily in the cytoplasmic and cellular membrane compartments. However, its role in somatic cell nuclei has recently become evident where it participates in transcription, chromatin remodeling, and DNA damage repair. What remains enigmatic is the involvement of nuclear actin in physiological processes that lead to the generation of germ cells, in general, and primary spermatocytes, in particular. Here, we will discuss the possible role and nuclear localization of actin during meiotic prophase I and its interaction with chromatin remodeling complexes, the latter being essential for the control of pairing of homologous chromosomes, cross-over formation, and recombination. It is our hope that this perspective article will extend the scope of actin's nuclear function in germ cells undergoing meiotic division.